2007
DOI: 10.1007/s10342-006-0149-z
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal variability of stand structure and regeneration in the subalpine spruce forests of the Pol’ana biosphere reserve, Central Slovakia

Abstract: The structure of natural subalpine spruce forest in the Zadna´Pol'ana massif of the Western Carpathians was analysed. We focused on the variability of different aspects of stand structure, tree decay and regeneration processes in altitudinal gradient. We used systematic sampling, covering an area of 2 km 2 , to detect even subtle changes in stand structure within one forest type over a range of less than 200 m in elevation. Mean stand density was 290 trees (>7 cm DBH) per hectare, average basal area was 41 m 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 37 publications
7
46
2
Order By: Relevance
“…even the majority of the seedlings (more than 70%) are growing on elevations while slope and depression (micro-pan) are the micro-relief which does not represent preferable sites for seedling germination and growth. These facts are in accordance with Holeksa et al (2007).…”
Section: Discussionsupporting
confidence: 92%
“…even the majority of the seedlings (more than 70%) are growing on elevations while slope and depression (micro-pan) are the micro-relief which does not represent preferable sites for seedling germination and growth. These facts are in accordance with Holeksa et al (2007).…”
Section: Discussionsupporting
confidence: 92%
“…In all developmental stages of the virgin forest the number of individuals of both tree species decreases with the increasing altitude. Similar results were reported by Holeksa (1998) from the Polish part of the orographic unit Babia hora and from the orographic unit Poľana as well (Holeksa et al 2006). Concerning the seedbed types the results confirmed that 53% of spruce seedlings emerged on dead wood and 47% on mineral soil, while the proportion of dead wood was only 3.34%.…”
Section: Discussionsupporting
confidence: 89%
“…If we evaluate the tree distribution of the Norway spruce virgin forest on the basis of the aggregation index according to Clark and Evans (1954), our results confirm the findings from the Norway spruce natural forest in Poľana NNR (Holeksa et al 2006). The changes in the index values in relation to altitude are also nearly the same in this explored object.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…One of the key factors responsible for the lower regeneration of spruce in the extracted plots is the absence of dead wood, since it decreases the pressure of competitive species, for which decomposing material is not an optimal substrate [1,[35][36][37]. The importance of dead wood in forest regeneration increases at higher altitudes [38], and it also maintains the necessary microclimate and protects the seedlings from intensive sunlight. According to Rusek and Brůhová [39], the extraction of wood biomass negatively influences the structure of epigeic fauna which is an obligatory function of natural spruce forests.…”
Section: Natural Regeneration Of the Treesmentioning
confidence: 99%